Feasibility study of a point‐of‐care positron emission tomography system with interactive imaging capability. Issue 4 (14th February 2019) - Jiang, Jianyong; Li, Ke; Komarov, Sergey; O'Sullivan, Joseph A.; Tai, Yuan‐Chuan
Abstract : Purpose: We investigated the feasibility of a novel positron emission tomography (PET) system that provides near real‐time feedback to an operator who can interactively scan a patient to optimize image quality. The system should be compact and mobile to support point‐of‐care (POC) molecular imaging applications. In this study, we present the key technologies required and discuss the potential benefits of such new capability. Methods: The core of this novel PET technology includes trackable PET detectors and a fully three‐dimensional, fast image reconstruction engine implemented on multiple graphics processing units (GPUs) to support dynamically changing geometry by calculating the system matrix on‐the‐fly using a tube‐of‐response approach. With near real‐time image reconstruction capability, a POC‐PET system may comprise a maneuverable front PET detector and a second detector panel which can be stationary or moved synchronously with the front detector such that both panels face the region‐of‐interest (ROI) with the detector trajectory contoured around a patient's body. We built a proof‐of‐concept prototype using two planar detectors each consisting of a photomultiplier tube (PMT) optically coupled to an array of 48 × 48 lutetium‐yttrium oxyorthosilicate (LYSO) crystals (1.0 × 1.0 × 10.0 mm 3 each). Only 38 × 38 crystals in each arrays can be clearly re‐solved and used for coincidence detection. One detector was mounted to a robotic arm which can position it at arbitrary locations, and the other detector was mounted on a rotational stage. A cylindrical phantom (102 mm in diameter, 150 mm long) with nine spherical lesions (8:1 tumor‐to‐background activity concentration ratio) was imaged from 27 sampling angles. List‐mode events were reconstructed to form images without or with time‐of‐flight (TOF) information. We conducted two Monte Carlo simulations using two POC‐PET systems. The first one uses the same phantom and detector setup as our experiment, with the detector coincidence re‐solving time (CRT) ranging from 100 to 700 ps full‐width‐at‐half‐maximum (FWHM). The second study simulates a body‐size phantom (316 × 228 × 160 mm 3 ) imaged by a larger POC‐PET system that has 4 × 6 modules (32 × 32 LYSO crystals/module, four in axial and six in transaxial directions) in the front panel and 3 × 8 modules (16 × 16 LYSO crystals/module, three in axial and eight in transaxial directions) in the back panel. We also evaluated an interactive scanning strategy by progressively increasing the number of data sets used for image reconstruction. The updated images were analyzed based on the number of data sets and the detector CRT. Results: The proof‐of‐concept prototype re‐solves most of the spherical lesions despite a limited number of coincidence events and incomplete sampling. TOF information reduces artifacts in the reconstructed images. Systems with better timing resolution exhibit improved image quality and reduced artifacts. We observed a reconstruction speed of 0.96 × 10 6 events/s/iteration for 600 × 600 × 224 voxel rectilinear space using four GPUs. A POC‐PET system with significantly higher sensitivity can interactively image a body‐size object from four angles in less than 7 min. Conclusions: We have developed GPU‐based fast image reconstruction capability to support a PET system with arbitrary and dynamically changing geometry. Using TOF PET detectors, we demonstrated the feasibility of a PET system that can provide timely visual feedback to an operator who can scan a patient interactively to support POC imaging applications. Abstract :